Change and Recovery: Culturally Appropriate Early Childhood Programmes with Refugee Families and Communities. (12th August 2015) - Signorelli, R. G.; Coello, M.; Momartin, S.; Tucci, Joe; Mitchell, Janise
<x content-type="archive" xml:space="preserve">Abstract</x> The STARTTerS Early Childhood Programme at the NSW Service for the Treatment and Rehabilitation of Torture and Trauma Survivors (STARTTS) has been developed in response to the complex refugee experiences of very young children, their families and communities. This biopsychosocial and systemic model is informed by neuroscience, attachment theory and current knowledge of the nature and impact of refugee-specific trauma on very young children and their families. It addresses the complex interactions between, social, cultural and political factors within the trauma and recovery environments, as they influence the clients' presentations and the choice of interventions with families in cultural transition (FICT). This paper provides a background to the STARTTerS programme, and reports on the results of a Community Based Participatory Research (CBPR) project with the Karen and Mandaean refugee communities. It explores perceptions and cultural views of signs and symptoms related to early childhood trauma. It also explores help seeking preferences in relation to the recovery, settlement and health needs of families with young children. This research has led to ongoing collaborative and consultative processes with those communities, resulting in the development of services and referral systems, which will build a comprehensive and culturally appropriate early childhood programme.